2015
DOI: 10.1128/aac.00885-15
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aminoglycoside Acetyltransferase Resistance Enzymes by Metal Salts

Abstract: Aminoglycosides (AGs) are clinically relevant antibiotics used to treat infections caused by both Gram-negative and Gram-positive bacteria, as well as Mycobacteria. As with all current antibacterial agents, resistance to AGs is an increasing problem. The most common mechanism of resistance to AGs is the presence of AG-modifying enzymes (AMEs) in bacterial cells, with AG acetyltransferases (AACs) being the most prevalent. Recently, it was discovered that Zn 2؉ metal ions displayed an inhibitory effect on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…1A and B). This result agrees with that recently observed in a similar study (22). We showed before that the chloride salt of Zn 2ϩ in combination with AMK induced inhibition of growth in Escherichia coli and Acinetobacter baumannii strains harboring aac(6=)-Ib; however, very high concentrations were required (19).…”
supporting
confidence: 93%
“…1A and B). This result agrees with that recently observed in a similar study (22). We showed before that the chloride salt of Zn 2ϩ in combination with AMK induced inhibition of growth in Escherichia coli and Acinetobacter baumannii strains harboring aac(6=)-Ib; however, very high concentrations were required (19).…”
supporting
confidence: 93%
“…This opposite effect may be due to the interference of metals with specific antibiotic resistance mechanisms. For instance, recent studies showed that Cu and Zn inhibit the activity of aminoglycoside acetyltransferases, which confer resistance to aminoglycosides (Li et al, 2015).…”
Section: Metal(loid)mentioning
confidence: 99%
“…Antibacterial action of flavonoid-metal complexes Havsteen (2002), in his voluminous paper on flavonoid properties, tried to explain the antibacterial activities of flavonoids. Since many studies showed the ability of flavonoids to chelate transition metal ions (Karlíčková et al 2015;Li et al 2015;Riha et al 2014;Samsonowicz et al 2017), he pointed out that many flavonoids could cause the inhibition of bacterial metal enzymes. This mechanism of action is common for many other antibacterial substances, including lactoferrin from human milk.…”
Section: Inhibition Of Electron Transport Chain and Atp Synthesismentioning
confidence: 99%